The importance of norepinephrine in depression - Moret, Chantal (Dove Medical Press, 2011)
Depression is one of the most common psychological diseases with significant potential morbidity and mortality. Although the underlying pathophysiology of depression has not been clearly defined, preclinical and clinical evidence suggest disturbances in serotonin (5-HT), norepinephrine (NE), and dopamine (DA) neurotransmission in the central nervous system. Virtually all currently available antidepressants act on one or more of the following mechanisms: inhibition of reuptake of 5-HT or NE (and DA), antagonism of inhibitory presynaptic 5-HT or NE receptors, or inhibition of monoamine oxidase. All of these mechanisms result in an enhanced neurotransmission of 5-HT and/or NE. Evidence for the involvement of NE in depression is abundant, and recent studies on neuronal pathways and symptoms highlight the specific role of NE in this disorder. NE plays a determinant role in executive functioning regulating cognition, motivation, and intellect, which are fundamental in social relationships. Social dysfunction is possibly one of the most important factors affecting the quality of life in depressed patients.